Applying and implementing future-oriented methods on a national level; towards enhanced policy and service preparedness to threats in the drugs domain - L. Gremeaux; Laura Smit-Rigter; John-Peter Kools (Annual ISSDP Conference - Drug market and Drug innovation in a changing world, 2022)
Background Developments in the area of drugs are evolving rapidly and new threats request countries to step up to address these challenges. Meanwhile, most drug policies and services are still grounded in response approaches that address issues of the past decades (e.g. problematic heroin and cocaine use). The current rise of prevalence and use of synthetic opioids (SO) in a number of countries in Europe stresses the need to become better prepared in order to prevent further harm. More innovation and future-oriented strategies are needed to address other current and future developments in the drug field. The presentation will first describe how to identify and respond to known and currently ongoing threats. The second part will describe how foresight research can contribute to national drug information systems for better preparedness and how it can be developed and implemented at national levels. Methods A combination of more traditional multi-source qualitative research (literature research, Reitox workbook consultations, key stakeholder interviews and focus groups) is combined with more innovative future-oriented approaches (e.g. horizon scanning, scenario development and back-casting). Outcomes are used to actively support research agencies, policymakers and services. Multiple workshops and national dialogues will be facilitated in order to implement these methods on a national level. Results On preparedness of the known threat of Synthetic Opioids. Research indicates that European countries are likely to face increases in prevalence and use of SO. All countries in Europe are recommended to become well prepared in terms of monitoring and responses. In order to support that process a set of implementation guides on effectively respond to synthetic opioids substances is developed. On preparedness to currently ongoing threats. Through literature research and questionnaires to Reitox National Focal Points and through a European civil society network, the current situation in Europe in terms of patterns in drug use, people who use drugs, societal developments, patterns in drug markets has been summarized. On a national level, drug researchers and policy makers can use this information to respond accordingly. Foresight research is applied on a European and on a national level (in 6 countries) for the  identification of possible threats in the (mid-term) future that are shaped by current societal developments. On the basis of this scanning exercise, various response national scenarios will be developed and implications will discussed by national key stakeholders. Conclusions and discussion Multi-method research, using traditional and more innovative methods, is effective in supporting better monitoring and intervention activities. It proves useful in preparing for particular possible trends - like with SO - and it will be useful for other similar developments in substance prevalence, trade and consumption. In order to supports enhanced preparedness and resilience of European countries’ drug information and intervention capacity to respond to emerging drug trends and threats, intensified research and applied implementation support is highly recommended. Targeted foresight research is a very useful instrument for national observatories, policy makers and civil society to get better insight and understanding in possible upcoming developments and respond accordingly. In becoming better prepared for the future.
Keywords: Drug policy; Foresight; illicit drugs